Migration experiences of south american women faculty in two mexican public universities - Izquierdo, Isabel; Estrada, Olga Nelly (Universidade Estadual de Campinas, 2019)
The aim of the article is to analyze the experiences of migration of South American women scholars, their arrival and incorporation in two Mexican universities, one in the center-south and another located in the north-east of the country. We assume that in their migratory process, the academics acquired a series of experiences that allowed them to implement strategies to move from stress situations to learning in that process. The biographical method was used, through life stories, interviewing scholars who mostly come from South American countries. The findings showed that scholars launched strategies of mimicry, creativity, pragmatism and perseverance, despite differences in socioeconomic development of states and research development in public universities where they work.